A large and complex saccular external jugular vein aneurysm in an adolescent girl - Claire A. Ostertag-Hill; Danielle B. Cameron; Leonardo R. Brandão; Philip R. John; Heung Bae Kim; Steven J. Fishman (Elsevier, 2021)
Venous aneurysms of the head and neck region are very uncommon. Aneurysms of the external jugular vein in children are exceedingly rare, and consequently the best approach to diagnosis and management has not been clearly defined. We present the case of a 15-year-old girl with a non-pulsatile, occasionally painful, enlarging fullness in her right supraclavicular fossa and neck. Imaging demonstrated a large and complex right external jugular vein aneurysm with thrombus. Given the symptomatic nature of this aneurysm, recurrent episodes of thrombosis, and the risk of thromboembolism, she underwent surgical excision. Thorough pre-operative planning with additional imaging to better understand the anatomy of this aneurysm was critical to a safe and successful intervention.